The pertinence of genetic screening in gamete donors (2012)
Introduction: A major concern for pairs undergoing assisted reproduction treatment with donated gametes is the possibility of acquiring infectious diseases or transmitting genetic diseases to their offspring. Some reports have been based on the legislation of each country and each centre's experience referring to the type of genetic infectious and/or psychological evaluation which gamete donors must undergo. There is no specific law in Colombia about assisted reproduction and/or gamete donor techniques; also, there is no clarity about whether donors should be genetically evaluated and which type of test should be used for this. Objective: This document was aimed at making a reflection about the pertinence of genetically evaluating gamete donors by characterising the main genetic conditions prevailing in the Colombian population, base genetic alteration and the method currently being used for genetic diagnosis. Conclusion: It was concluded that a clear national protocol must be developed about genetic evaluation in gamete-donating patients; this should also be done in assisted reproduction centres.